Effects and mechanisms of pyrethroids on male reproductive system. (30th May 2020) - Wang, Qi; Shen, Jun-Yu; Zhang, Rui; Hong, Jia-Wei; Li, Zheng; Ding, Zhen; Wang, Heng-Xue; Zhang, Jin-Peng; Zhang, Mei-Rong; Xu, Li-Chun
Abstract: Synthetic pyrethroids are used as insecticides in agriculture and a variety of household applications worldwide. Pyrethroids are widely distributed in all environmental compartments and the general populations are exposed to pyrethroids through various routes. Pyrethroids have been identified as endocrine-disrupting chemicals (EDCs) which are responsible for the male reproductive impairments. The data confirm pyrethroids cause male reproductive damages. The insecticides exert the toxic effects on male reproductive system through various complex mechanisms including antagonizing androgen receptor (AR), inhibiting steroid synthesis, affecting the hypothalamic-pituitary-gonadal (HPG) axis, acting as estrogen receptor (ER) modulators and inducing oxidative stress. The mechanisms of male reproductive toxicity of pyrethroids involve multiple targets and pathways. The review will provide further insight into pyrethroid-induced male reproductive toxicity and mechanisms, which is crucial to preserve male reproductive health.